2014
DOI: 10.3141/2417-01
|View full text |Cite
|
Sign up to set email alerts
|

Bus Drivers’ Responses to Real-Time Schedule Adherence and the Effects on Transit Reliability

Abstract: Bus drivers have responded positively toward real-time bus information in various surveys. However, empirical studies on their actual responses are limited. On the basis of actual automatic vehicle location data, this study quantified bus drivers’ responses to real-time schedule adherence and their effects on transit reliability. Bus trips that were ahead of and behind schedule were analyzed separately at timepoint stops, regular stops, and along the roadways between stops. Results revealed that bus drivers wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Moreover, non-linearity in dwell time and driver behavior patterns could be embedded into the prediction scheme to better capture the complexity of public transport dynamics. There is empirical evidence that drivers adjust their speed in response to RTI on schedule adherence (Cats et al 2012, Ji et al 2014. This driving pattern could be potentially accounted for in future prediction schemes in line with Lin and Bertini (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, non-linearity in dwell time and driver behavior patterns could be embedded into the prediction scheme to better capture the complexity of public transport dynamics. There is empirical evidence that drivers adjust their speed in response to RTI on schedule adherence (Cats et al 2012, Ji et al 2014. This driving pattern could be potentially accounted for in future prediction schemes in line with Lin and Bertini (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Such schedule recovery effort is widely adopted in the context of advanced public transport systems (APTS) (e.g. Yan et al, 2012;Lin and Bertini, 2004;Chen et al, 2005;Ji et al, 2014). However, to simplify the model, in this study we use a continuum approach to develop a closed-form expression to capture such interaction; we describe the approach in the model formulation section.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The reduction in tram travel time was obtained without sacrificing the mobility of through traffic. Empirical studies have revealed that transit drivers would respond positively to real-time information to keep on schedule [28]. That is, drivers will adjust speeds along the roadways and dwell times at stations to keep on schedule.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%